Cervical cytopathological changes associated with onset of menopause - Jata Shanker Misra; Anand Narain Srivastava; Zeeshan Haider Zaidi (Wolters Kluwer Medknow Publications, 2018)
Background: In the life of a woman, after 40 years of age, onset of menopause occurs during which hormonal imbalances take place. The present study is aimed at finding out cytopathological changes in the cervical epithelium associated with this hormonal disturbance. Materials and Methods: Cervical cancer screening program is in progress under auspices of Era's Lucknow Medical College and Hospital, Lucknow, since May 2013, in the villages of Lucknow West through camp approach. Till September 2017, 140 camps have been organized and 2440 women attending the camp have been cytologically examined. Out of these, 1534 women were perimenopausal, 165 premenopausal, and 441 postmenopausal. The cytopathological changes have been studied in these three categories of women in relation to different predisposing factors to the cervical carcinogenesis. Results: The squamous intraepithelial lesion (SIL) rate was higher with onset of menopause in the premenopausal women. The SIL rate was higher with nulliparity in these women as well as in the postmenopausal women and also with different gynecological symptoms and clinical lesions of the cervix. The SIL changes associated with HPV and HSV were also higher in them. Conclusion: A high SIL rate found with onset of menopause may be the outcome of gradual estrogen withdrawal in the premenopausal women. Hence, cytological evaluation is mandatory in women between 41 and 45 years of age to rule out any occurrence of cervical cytopathology.